Pemakaian Crown Loop dan Band Loop di Rahang Bawah Anak Usia Enam Tahun (Laporan Kasus) - Rivi Isabela; Hendrarlin Soenawan (Faculty of Dentistry, Universitas Indonesia, 2015)
The function of space maintainer is to preserve arch length following the premature loss of a primary teeth. Early loss of primary tooth may compromise the eruption of succedaneous teeth if there is a reduction in the arch length. The Band and Crown Loop are used to maintain the loss of primary molar. The report describe a 6 year old girl who has premature loss of second left mandibular primary molar and first right mandibular primary molar treated using crown and band loop space maintainer. The patient still has mastication function from other posterior primary teeth.